Convergence and divergence of role stress experience of locally hired Japanese and non-Japanese host country staff: a qualitative study - Okamoto, K.; Teo, Stephen (Routledge, 2011)
This qualitative study examines the role stress (comprising of role ambiguity and role conflict) experienced by locally hired Japanese (LJ) and non-Japanese (NJ) staff in a sample of Japanese companies in Australia. Expatriates were also interviewed to gather information regarding the impact of cross-cultural understanding on role ambiguity and role conflict in their work relationships with LJ and NJ staff. Both LJ staff and NJ local staff experienced two types of role ambiguity, resulting from insufficient English competence and information shortage. NJ staff experienced two additional types of role ambiguity due to their lack of cultural understanding about Australia, and their Japanese cultural heritage and understanding of the society and organisational processes. This study shows that cultural understanding of one's host country and parent country could reduce role ambiguity. In addition, it was found that cultural understanding of one's host country and parent country results in role conflict. These findings suggest that cultrual understanding could have positive and negative consequences on role stress. Theoretical and practical implications in the management of white-collar staff in overseas Japanese companies are discussed.